Pengaruh Ketidakpuasan Konsumen dan Kebutuhan Mencari Variasi terhadap Keputusan Perpindahan Merek Produk Vitamin C di Surabaya Timur - Lilik Indrawati (Universitas Negeri Surabaya, 2018)
The availability of vitamin C products increases on the market with various types so that buyers also require consideration in purchasing these products. Brand switching behavior which occurs due to variety seeking behavior needs to receive attention from marketers. This behavior tends to happen in products that require low levels of involvement or when the consumer does not involve many factors of consideration and information obtained prior to the purchase decision is taken. This study aims to see how the influence of consumer dissatisfaction and the need to find the product variety toward Vitamin C product brand switching decisions in Surabaya. This is a conclusive study that was conducted by distributing questionnaires. The independent variables are consumer dissatisfaction and the need of seeking variation, while the dependent variable is the brand switching decision. The research method used is a multiple linear regression. Data will be processed by using SPSS software with 100 samples. The result showed that consumer dissatisfaction (X1) and the need of seeking variation (X2) has a very significant influence on the brand switching decision shown by the results of F test, using SPSS 12, in which F-count > F-table, which is 78.860> 3.09. In conclusion, the independent variable, namely consumer dissatisfaction and the need of seeking variation, gives a significant influence on the brand switching decision simultaneously. Consumer dissatisfaction variable (X1) has a t-count (3.619)> t-table (1.985) and the need of seeking variation variable (X2) has a t-count (6.828)> t-table (1.985), so it can be concluded that both of them influence the brand switching decision (Y) partially. The need of seeking variation variable is the dominant factor. Therefore, vitamin C products should be created according to consumer expectations, such as improving the ability of product durability, and add other content to keep them healthy.